Molecular phylogeny and morphology reveal a new wood-inhabiting fungal species of Conferticium (Stereaceae, Basidiomycota) from southwest China - Shen, Lulu; Wang, Kunyan; Xia, Hui; Liu, Shiling; Yao, Lu; Yang, Xin (Phytotaxa, 2024)
A new wood-inhabiting fungus, Conferticium fissuratum is proposed based on morphological features and molecular phylogenetic evidence. It is characterized by the membranous basidiomata with the tuberculate hymenial surface, a monomitic hyphal system having simple-septate generative hyphae, the presence of the subcylindrical cystidia with the mastoid process and broadly ellipsoid, and the verrucose basidiospores (4.5–6.1 × 3.5–4.7 µm). The phylogenetic tree inferred from ITS sequences revealed that the new species C. fissuratum clusters sister to C. ravum. A full description, illustrations, and results of the phylogenetic analysis of the new species are provided.